Aplikasi Inventaris Aset Barang Bekas pada Hotel Rattan In Banjarmasin Berbasis Web - Yudha Iman (mijournal.org, 2026)
The hospitality business in Banjarmasin City is growing rapidly. Hotel management conducts facility refreshes through maintenance or new purchases financed by selling replaced or damaged assets. Hotel Rattan In Banjarmasin manages damaged facilities stored in temporary and central warehouses. Weak monitoring leads to difficulty inventorying used assets and risks item loss. This study develops a Web-based Used Asset Inventory Application for Hotel Rattan In Banjarmasin using the Waterfall software development methodology. Tools include Notepad++, PHP, MySQL, XAMPP, and DFD modeling. The results demonstrate that the web application effectively tracks asset status (repaired, sold, or destroyed), improves inventory accuracy, and generates financial sales reports efficiently.